Mindfulness, Resilience, and Burnout Subtypes in Primary Care Physicians: The Possible Mediating Role of Positive and Negative Affect - Montero-Marin, Jesús; Tops, Mattie; Manzanera, Rick; Piva Demarzo, Marcelo M.; Álvarez de Mon, Melchor; García-Campayo, Javier (Frontiers in Psychology, 2015)
Abstract Purpose: Primary care health professionals suffer from high levels of burnout. The aim of the present study was to evaluate the associations of mindfulness and resilience with the features of the burnout types (overload, lack of development, neglect) in primary care physicians, taking into account the potential mediating role of negative and positive affect. Methods: A cross-sectional design was used. 622 Spanish primary care physicians were recruited from an online survey. The Mindful Attention Awareness Scale (MAAS), Connor-Davidson Resilience Scale (CD-RISC), Positive and Negative Affect Schedule (PANAS) and Burnout Clinical Subtype Questionnaire (BCSQ-12) questionnaires were administered. Polychoric correlation matrices were calculated. The unweighted least squares method was used for developing structural equation modelling. Results: Mindfulness and resilience presented moderately high associations (φ=0.46). Links were found between mindfulness and overload (γ=-0.25); resilience and neglect (γ=-0.44); mindfulness and resilience, and negative affect (γ=-0.30 and γ=-0.35 respectively); resilience and positive affect (γ=0.70); negative affect and overload (β=0.36); positive affect and lack of development (β=-0.16). The links between the burnout types reached high and positive values between overload and lack of development (β=0.64), and lack of development and neglect (β=0.52). The model was a very good fit to the data (GFI=0.96; AGFI=0.96; RMSR=0.06; NFI=0.95; RFI=0.95; PRATIO=0.96). Conclusions: Interventions addressing both mindfulness and resilience can influence burnout subtypes, but their impact may occur in different ways, potentially mediated by positive and negative affect. Both sorts of trainings could constitute possible tools against burnout; however, while mindfulness seems a suitable intervention for preventing its initial stages, resilience may be more effective for treating its advanced stages.